Large-Scale Environment Properties of Narrow-Line Seyfert 1 Galaxies at z < 0.4 - Järvelä, Emilia; Lähteenmäki, A.; Lietzen, H. (Frontiers in Astronomy and Space Sciences, 2017)
The large-scale environment is believed to affect the evolution and intrinsic properties of galaxies. It offers a new perspective on narrow-line Seyfert 1 galaxies (NLS1) which have not been extensively studied in this context before. We study a large and diverse sample of 960 NLS1 galaxies using a luminosity-density field constructed using Sloan Digital Sky Survey. We investigate how the large-scale environment is connected to the properties of NLS1 galaxies, especially their radio loudness. Furthermore, we compare the large-scale environment properties of NLS1 galaxies with other active galactic nuclei (AGN) classes, for example, other jetted AGN and broad-line Seyfert 1 (BLS1) galaxies, to shed light on their possible relations. In general NLS1 galaxies reside in less dense large-scale environments than any of our comparison samples, thus supporting their young age. The average luminosity-density and distribution to different luminosity-density regions of NLS1 sources is significantly different compared to BLS1 galaxies. This contradicts the simple orientation-based unification of NLS1 and BLS1 galaxies, and weakens the hypothesis that BLS1 galaxies are the parent population of NLS1 galaxies. The large-scale environment density also has an impact on the intrinsic properties of NLS1 galaxies; the radio loudness increases with the increasing luminosity-density. However, our results suggest that the NLS1 population is indeed heterogeneous, and that a considerable fraction of them are misclassified. We support a suggested description that the traditional classification based on the radio loudness should be replaced with the division to jetted and non-jetted sources.